Study on decontamination of microorganisms in garlic powder by gamma Co-60 radiation - Vo , Thi Kim Lang; Nguyen , Thuy Khanh; Doan , Thi The; Nguyen , Thi Tu Trinh (Nuclear Science and Technology, 2013)
Garlic powder was irradiated by gamma-rays from a Co-60 source to reduce microbial contamination for prolong the storage and preservation time. Results showed that the initial microbial number of about 106CFU/g contaminated in garlic powder was exceeded for the set standard of TCVN 7809 – 2007 and ISO 5560 – 1997. The total aerobic bacteria and yeast mold cells of irradiated garlic powder were reduced from 106 CFU/g to 104, 6103 and 6102 CFU/g at doses of 0, 4, 8 and 12 kGy, respectively. The level of microbial contamination was significantly reduced by irradiation at 4 kGy but it is only appropriate for domestic acceptance. At the irradiation doses of 8 and 12 kGy, the level of microbial contamination was further reduced after storage for two months and it is appropriate to export. In addition, the irradiated garlic powder was in good quality with no change of moisture, oil content and sensory properties. Thus, gamma Co-60 irradiation is a very effective method for reducing the number of microbial contaminated in garlic powder.